THE DECENTRALISATION OF EDUCATION IN KERALA STATE, INDIA: RHETORIC AND REALITY - MULLIKOTTU-VEETTIL MUKUNDAN and MARK BRAY (International Review of Education 50: 223-243, 2004., 2004)
The decentralisation of educational administration has been widely advocated as a strategy to promote local participation in education. However, the fact that this advocacy has a long history raises the question why decentralisation has not been achieved in more educational systems. The answers to this question are many and complex. Among them are difficulties with the implementation of reforms. The present study examines some of these difficulties in Kerala State, India. It determines that although Kerala has a strong reputation for political participation, the rhetoric of decentralisation in the educational sector has not matched the reality there. The lessons to be learned in this context have wide implications for the theory and practice of decentralisation in education.